Electromechanical Behavior of Helical Auxetic Yarn Strain Sensor - Asal Lolaki; Saba Sajjadieh; Mahsa Peidani; Zahra Rafieian; Hamed Rezaie; Mohsen Shanbeh (Engineering Proceedings)
Three-component strain sensors based on helical auxetic yarn (HAY) structure were designed. HAYs comprise elastic core yarn, wrapped by the composition of multifilament Nylon 66 and conductive spun yarns with three different electrical resistance. The electromechanical behavior of samples was investigated. The cross-section of samples was studied to investigate the aerial density of conductive fibers at different strain ranges. The results indicated that gauge factors of HAY strain sensors significantly depend on the electrical resistance of the conductive component. Therefore, a new generation of efficient wearable textile-based strain sensors is introduced, based on the adjustable and flexible nature of the auxetic yarns.